(untitled) (Research, Society and Development, 2018)
Legal-constitutional norms consist of a fertile field of research available for conducting educational research. The purpose of this study is to present the administrative measures taken by the Provincial Legislative Assembly for the organization of the primary education system in Rio Grande do Sul, following the promulgation of the Additional Act of 1834. For the composition of the information registered here, being necessary for analysis and reflection on educational events in their historical trajectory. In addition to the documentary research, using as sources for the study two indispensable productions: the "Collection of Documents of the Brazilian Education" in which are cataloged and organized 46 official documents that regulated the Public Instruction in the Province of Rio Grande do Norte; the book "A Century of Primary Education" of historian Nestor dos Santos Lima published in 1927 to analyze the benefits caused by the General Law of October 15, 1827, as an essential framework for the perception of the educational transformations of the Province of Rio Grande do Norte. With the bibliographical and sources survey, we noticed that in terms of legislation there was an incessant attempt to organize teaching in that province. Our first impressions are that the North-Rio Grande Legislative Assembly was active during the period of decentralization experienced by imperial education, showing care in the administrative and systematic organization of teaching.